Potential benefit of using phenazopyridine to detect multiple vesicovaginal fistulas for primary repairs on medical mission trips in Cote d'Ivoire - Matthew A. Geisler; Kelly J. Manahan; John P. Geisler (Clinical and Experimental Obstetrics & Gynecology)
Background: Vesicovaginal fistulas are complex medical/surgical issue that may arise after obstructed labor in areas without access to maternal health care providers. In some areas, fistulas have devastating social consequences on the patient. Easier visualization of the fistula during the surgery might contribute to better surgical success. For this purpose, we describe the use of inexpensive, humble methods available in resource-limited areas. The drug phenazopyridine makes urine orange, whereby easing visualization of fistula(s) during surgery. The objective of this study was to determine the effectiveness of phenazopyridine administration in the resource limited settings. Methods: Medical record review was conducted. Data has been prospectively followed from all patients with vesicovaginal fistulas. All cases were staffed by experienced gynecologic oncologists with multiple different medical trainees (American and Ivorian) assisting. For the first 3 mission trips, no phenazopyridine was given pre-operatively. For the fourth to ninth trip, phenazopyridine was given preoperatively along with enhanced recovery medications. All patients had transurethral catheters left in place for 2 weeks that were removed by a medical professional. Imaging was not available and so success of the repair was based on patient reported symptoms after removal. Patient outcomes (subjective success by patient report) were compared between the two groups (without versus with phenazopyridine). Two-tail Chi square statistics with a significance of 0.05 were performed. Results: 53 patients with vesicovaginal fistulas arising after obstructed labor were primarily treated during nine two-week mission trips. Another 5 patients had urethral vaginal fistulas and these were not included in the report. Of the 53 patients, 9 patients also had co-existing rectovaginal fistulas that were repaired at the same time. The first group of 17 vesicovaginal fistulas (no phenazopyridine given) had a success rate of 76.5% (13/17) while the second group (phenazopyridine given) had a success rate of 97.2% (35/36) (p = 0.016). At the same time the rate of multiple vesicovaginal fistulas in the same patient changed from 5.8% (1/17) in the first group to 22.2% (8/36) (p = 0.14). Conclusions: Using phenazopyridine pre-operatively aided the surgeons in diagnosing multiple vesicovaginal fistulas more commonly and may have benefitted patients by leading to a higher surgical success rate.